EFEKTIVITAS KOMUNIKASI PENYULUHAN DEMAM BERDARAH DENGUE (DBD) OLEH DINAS KESEHATAN KOTA PEKANBARU KEPADA MASYARAKAT DI KECAMATAN BUKIT RAYA - Retno Puji Pertiwi; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Communication information about Dangue Hemorrhagic Fever (DHF) is a routine activity carried out by the Pekanbaru City Health Service. Counseling was held both in the lecture method at the puskesmas in Bukit Raya District and by using the mobile method. The theory used in this research is Effectiveness theory. The purpose of this study was to find out how much the effectiveness of Dengue Hemorrhagic Fever (DHF) communication by the Pekanbaru City Health Service to the community in Bukit Raya sub-district. This study uses a quantitative research method with a descriptive approach, with data collection techniques, namely through distributing questionnaires to the people of Bukit Raya Sub-district who participated in DHF counseling with a sample of 166 respondents determined through Accidental Sampling techniques caused by accidental nature. While the data analysis technique in this study uses desktiptif statistical techniques. The results of this study indicate that the level of Communication Effectiveness of DHF Counseling conducted by the Pekanbaru City Health Office is very effective with a scale of 3.27. The message receiver indicator (receiver) has a scale of 3.70, a scale of 3.48 on the message content indicator (content), a scale of 3.00 on the channel indicator (media), a scale of 3.20 on the indicator indicator, a scale of 3.13 on the indicator source message (source), and scale 3.17 on the indicator of timeliness (timings). Based on the results of the calculation of the effectiveness of DHF counseling communication obtained the results of 3.28 which shows a Very Effective scale. Thus it can be concluded that the Pekanbaru City Health Office has very effective communication in delivering and providing information on dengue counseling to the Bukit Raya District community.